2022
DOI: 10.1029/2021wr031215
|View full text |Cite
|
Sign up to set email alerts
|

Bluecat: A Local Uncertainty Estimator for Deterministic Simulations and Predictions

Abstract: We present a new method for simulating and predicting hydrologic variables with uncertainty assessment and provide example applications to river flows. The method is identified with the acronym “Bluecat” and is based on the use of a deterministic model which is subsequently converted to a stochastic formulation. The latter provides an adjustment on statistical basis of the deterministic prediction along with its confidence limits. The distinguishing features of the proposed approach are the ability to infer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…However, the modelling of the entire system cannot be reliably made without data and without moving from a deterministic to a stochastic description (cf. [12,13]). Therefore, induction is absolutely necessary.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the modelling of the entire system cannot be reliably made without data and without moving from a deterministic to a stochastic description (cf. [12,13]). Therefore, induction is absolutely necessary.…”
mentioning
confidence: 99%
“…It is true that some of the mechanisms of the transformation are described by differential equations as dynamical systems. However, the modelling of the entire system cannot be reliably made without data and without moving from a deterministic to a stochastic description (cf [12,13]…”
mentioning
confidence: 99%
“…et al (2019, 2020b), Tyralis et al (2019a, Sikorska-Senoner and Quilty (2021), Koutsoyiannis and Montanari (2022), Quilty et al (2022), Romero-Cuellar et al (2022)]. Notably, reviews, overviews and popularizations that focus on the above-referred to as existing and useful machine learning concepts and methods are currently missing from the probabilistic hydrological post-processing and forecasting literatures.…”
Section: Figurementioning
confidence: 99%
“…Hybridisation has emerged as a promising technique for overcoming numerous drawbacks of standalone methods while also improving prediction accuracy (Hajirahimi & Khashei, 2022). There are several types of hybrid models, e.g., the hybrid model that combines a physical model and a machine learning model (Nualtong et al, 2021;Xu et al, 2019), and the hybrid stochastic-ML model proposed by Koutsoyiannis and Montanari (Koutsoyiannis & Montanari, 2022). Papacharalampous (Papacharalampous et al, 2019) showed that the hybrid stochastic-ML model is better than single stochastic or ML models.…”
Section: Introductionmentioning
confidence: 99%